2012
DOI: 10.1143/apex.5.053004
|View full text |Cite
|
Sign up to set email alerts
|

Spin Accumulation and Spin Lifetime in p-Type Germanium at Room Temperature

Abstract: The electrical creation and detection of spin accumulation in p-type Ge were successfully demonstrated at room temperature by spin-polarized tunneling in epitaxial Fe/MgO contacts on Ge with a hole concentration of 8×1018 cm-3. In Hanle measurements, the spin accumulation produces a spin signal of about 40 µV per mA of tunnel current. The extracted spin lifetime of holes is 13 ps, which is much longer than the momentum relaxation time. The corresponding spin-diffusion length is 80 nm, suggesting that communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 28 publications
6
65
0
Order By: Relevance
“…The spin RA product also displays an exponential variation with thickness of the tunnel oxide, and a power law is revealed when the spin RA product is plotted against tunnel resistance [see Figs [20,21], we also find that R tun and the spin RA product vary exponentially with MgO thickness [see Fig. 3(c)], although the data set is too limited to extract an accurate value for the scaling exponent.…”
Section: Scaling With Tunnel Barrier Thicknessmentioning
confidence: 74%
See 1 more Smart Citation
“…The spin RA product also displays an exponential variation with thickness of the tunnel oxide, and a power law is revealed when the spin RA product is plotted against tunnel resistance [see Figs [20,21], we also find that R tun and the spin RA product vary exponentially with MgO thickness [see Fig. 3(c)], although the data set is too limited to extract an accurate value for the scaling exponent.…”
Section: Scaling With Tunnel Barrier Thicknessmentioning
confidence: 74%
“…Tunnel devices on p-type Ge(001) were prepared using Ga-doped wafers with a resistivity of 3 m cm and a carrier concentration of 8.2 × 10 18 cm −3 at 300 K. The preparation of the epitaxial MgO/Fe tunnel contacts on Ge was as previously described [21].…”
Section: Device Fabricationmentioning
confidence: 99%
“…[23][24][25] as well as into Ge through MgO. [26][27][28][29][30][31][32][33][34] Among the latest experiments, the transformation of a spin-polarized electron current into left-or righthanded circularly polarized light in a spin light-emitting diode (spin LED) integrating a III-V semiconductor heterostructure 8,11,[13][14][15][16][17]19,23,34,35 is one of the most striking physical phenomena. The electric dipolar selection rules involved in a quantum well 36 (QW) embedded in a spin LED during electron-hole recombination require spin injection with an out-of-plane magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Spin related properties such as spin injection efficiency from a ferromagnetic metal (FM) into a SC and spin lifetime in the SC were also discussed by analyzing the spin accumulation signals [1][2][3][4][5][6][7][8][9][10][11]. However, reliability of the estimated values of the spin related properties is now open for discussion.…”
mentioning
confidence: 99%
“…Hereafter, we focus on the effect of the magnetic domain structure in the FM contact used on the spin accumulation signals as one of the possible origins of the discrepancies between theories and experiments, because variously-sized FM contacts which can give rise to various magnetic domain structures have so far been utilized for the 3T measurements in the previous studies [1][2][3][4][5][6][7][8][9][10][11]. For the spin valve devices with multiple FM contacts which can detect the spin accumulation after intermixing of whole injected spins, it has been revealed that the magnetic domain structure of the spin injector strongly affects the spin accumulation signals [13].…”
mentioning
confidence: 99%